Lead Mining and the Survival and Demise of French in Rural Missouri - Gold, Gerald (Cahiers de géographie du Québec, 1979)
Old Mines is just about all that remains of French Missouri, a remnant of eighteenth century French and Spanish colonial ambitions. Rich lead deposits attracted the early French to what is now Washington county. The demand for hand dug lead (tuf) and later barite permitted French miners to continue their mode of production with its linguistic and cultural complementarities until World War II. Since, the Missouri French have been gradually disappearing. Yet even at moments of virtual cultural and linguistic collapse, voices are raised in an effort to rectify the situation.